Metabolic syndrome and survival of patients with hepatocellular carcinoma: A meta-analysis - Fu, Jia; Jiang, Jinqiong; Liu, Kanghan (Frontiers in Oncology, 2023)
Background: Metabolic syndrome (MetS) has been related to a high incidence of hepatocellular carcinoma (HCC). However, the influence of MetS on survival of patients with HCC is still unclear. We performed a systematic review and meta-analysis to evaluate the association between MetS and survival of HCC patients. Methods: A search of PubMed, Embase, and Web of Science retrieved relevant cohort studies from the inception of the databases to October 16, 2022. Data collection, literature search, and statistical analysis were carried out independently by two authors. We pooled the results using a random-effects model that incorporates heterogeneity. Results: In the meta-analysis, 8080 patients with HCC were included from ten cohort studies, and 1166 patients (14.4%) had MetS. Eight studies included patients treated primarily with radical hepatectomy, one study with patients receiving sorafenib, and another study included patients who were treated with radical hepatectomy or non-surgical treatments. Pooled results showed that MetS was associated with poor overall survival (OS, risk ratio [RR]: 1.21, 95% confidence interval [CI]:1.08 to 1.37, p = 0.001; I2 = 32%) and progression-free survival (PFS, RR: 1.33, 95% CI: 1.18 to 1.49, p < 0.001, I2 = 14%). Influencing analysis by excluding one study at a time showed consistent results (p all < 0.05). Subgroup analyses showed similar results in studies with MetS diagnosed with the National Cholesterol Education Program Adult Treatment Panel III or International Diabetes Federal criteria, and in studies with mean follow-up durations < or ≥ 3.5 years (p for subgroup difference all > 0.05). Conclusion: In patients with HCC, MetS may be a risk factor of poor OS and PFS, particularly for those after radical hepatectomy.